METHODOLOGY FOR ESTIMATION OF ECOLOGICAL SAFETY IN THE AGRICULTURAL OF UKRAINE - Oleksii SHKURATOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is devoted to research and development of methods for estimation of ecological safety in the agricultural area of the region's economy based on a comprehensive analysis of the main criteria and indicators that allow us to make motivated management decisions to prevent environmental threats and risks in this area. The methodology provides for the account of the integral index of ecological safety in the agricultural, which is defined as the sum of the normalized values of indicators (characterized by the corresponding indicator), taking into account the respective weighting coefficients. It is assumed that the difference in the dimensions of the parameters to be measured is eliminated by normalizing (transferring them to a dimensionless form). The estimation of the level of ecological safety in the agricultural of the regions of Ukraine has been carried out on the basis of the developed methodology. The distribution of the territory of Ukraine has been carried out on the following levels of ecological safety: stable, unsatisfactory, critical, crisis and dangerous. In general, the realization of the proposed methodology makes it possible to identify the features and trends of the ecological situation in the agricultural area of the region's economy in order to level out environmental contradictions in the form of a deviation between the actual and target state of agroecosystems in the process of balanced development of agriculture.